The Anterior Ventriculo-Cisternostomy: The Pioneers' Work Revisited - Mura, Jorge; Figueiredo, Eberval G.; Carmona, Pablo; Palma-Fellemberg, Álvaro; de Faria, José Weber V. (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2013)
Background There is no satisfactory medical treatment for hydrocephalus and most often surgical treatment is necessary, including shunting or endoscopic third ventriculostomy (ETV), both with their well-known advantages and drawbacks. The objective of this study is to describe a contemporary series of anterior ventriculocisternostomy.Patients Twenty-two patients with hydrocephalus treated at two institutions between 2005 and 2009 were presented. The authors employed a technique called anterior ventriculocisternostomy to treat selected cases. This technique includes supraciliary incision, small craniotomy, and fenestration of the lamina terminalis and Liliquist membrane. Hydrocephalus was secondary to hemorrhage from arteriovenous malformation (3 cases), spontaneous subarachnoid hemorrhage (2 cases), posterior fossa tumors (4 cases), head injury (1 case), basilar aneurysm (1 case), and posterior fossa hemorrhage (1 case). Eight patients had a normal-pressure hydrocephalus syndrome and one patient a slit ventricle syndrome. Aqueduct obstruction was noticed in one patient. Patients were followed up for 20.2 months (range: 10 to 46 months).Results No hemorrhagic complications or parenchymal injury were observed. One cerebrospinal fluid leakage occurred. No infection, mortality, and neurological morbidity were reported. Improvements were noticed in 18 cases. Eighty-two percent of the patients remained independent of shunt.Conclusion Anterior ventriculocisternostomy integrates old views of open ventriculocisternostomy with contemporary concepts of minimally invasive neurosurgery. It provides the most straightforward anatomical and physiological alternative to treat many types of hydrocephalus with no significant morbidity. Compared with conventional procedures, it has several advantages. This procedure is an important option to manage hydrocephalus and constitutes a safe, effective, and relatively inexpensive alternative to ETV and shunts.
Keywords: hydrocephalus; endoscopic surgery; minimally invasive neurosurgery; subfrontal approach; ventriculostomy; ventriculo-peritoneal shunt